619.KINEMATIC MODELLING AND ANALYSIS OF SERIAL MANIPULATOR - Simona, Domazetovska; Hristijan, Mickoski; Marjan, Djidrov (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
The purpose of this paper is modelling and simulation of serial manipulator type with four rotating joints (RRRR). CAD model was developed by using the software SolidWorks for modelling the serial manipulator. Simulation model of serial robot is made by conversion from SolidWorks to Matlab/Simulink. The serial robot can be shown schematic as a kinematic connection of rigid bodies that are interconnected using rotary kinematic pairs. The manipulator movement is defined so the movement of each member is related to the previous one. The position and orientation of the gripper must be defined to ensure safe handling. In this paper, the steps needed to model the serial manipulator together with all its components, its transfer into Simulink and its Proportional Integral Derivative (PID) controlling and simulation is described. The obtained results for velocity and acceleration in kinematic pairs contribute in detailed analysis of kinematics and control design.